2011
DOI: 10.1113/jphysiol.2011.209924
|View full text |Cite
|
Sign up to set email alerts
|

(–)‐Epicatechin enhances fatigue resistance and oxidative capacity in mouse muscle

Abstract: Non-technical summary During exercise, skeletal muscle performance depends in great part on the use of aerobic metabolism to supply the energetic demand of contractions. Endurance training increases the muscle aerobic capacity, which is not only associated with enhanced exercise performance, but also with a decreased risk of cardiovascular and metabolic diseases. Recently, it has been shown that regular use of small doses of dark chocolate may result in similar health benefits to exercise training. We show her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
207
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(230 citation statements)
references
References 68 publications
21
207
2
Order By: Relevance
“…One study reported that (-)-epicatechin alone or together with exercise induced structural and metabolic adaptation in skeletal and cardiac muscle and improved endurance capacity [16]. Another study indicated that (-)-epicatechin treatment alone significantly increased mitochondrial signaling, and cumulatively enhanced exercise performance when combined with 8 weeks of exercise training [76].…”
Section: (-)-Epicatechinmentioning
confidence: 97%
“…One study reported that (-)-epicatechin alone or together with exercise induced structural and metabolic adaptation in skeletal and cardiac muscle and improved endurance capacity [16]. Another study indicated that (-)-epicatechin treatment alone significantly increased mitochondrial signaling, and cumulatively enhanced exercise performance when combined with 8 weeks of exercise training [76].…”
Section: (-)-Epicatechinmentioning
confidence: 97%
“…Mice treated with epicatechin alone (without exercise) have structural and metabolic changes in skeletal and cardiac muscle similar to those of mice undergoing exercise (60). Epicatechin alone and in combination with exercise has an additive effect to stimulate myocardial angiogenesis (70).…”
Section: E682mentioning
confidence: 99%
“…The effect of EG on prostate cancer [55], and the effect of EC on prostate cancer, prevent stroke damage, fatigue resistance and oxidative capacity [56,60,61] has been previously described. Likewise, the effect of C and GC on blood circulation, fracture, chromic gastritis, rheumatoid arthritis and irregular menstruation has been shown [62].…”
Section: Medical Application Of Catechinmentioning
confidence: 99%